PENGARUH KEJELASAN SASARAN ANGGARAN AUDIT KINERJA DAN PERAN PERANGKAT DESA TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA - Sultan, Anisa Sultan; Rahmawati, Rahmawati; Junaidi (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The clarity of budget targets describes the breadth of budget targets that are clearly and specifically stated and understood by those responsible for their achievement and village officials who are part of the village government elements consisting of the village secretary and other village officials who are village officials under the auspices of the village head. This study is to test and re-analyze the effect of the clarity of performance audit budget targets and the role of devices on the accountability of village fund management. All village officials within the government of the eastern walenrang district of luwu district, totaling 8 villages in the walerang sub-district, were used as the population in this study and the sample in this study was 66 people. Then the data analysis method used to test the multiple linear regression hypothesis using SPSS. The results of this study indicate that the effect of performance audit budget target clarity has a positive effect on the accountability of village fund management and the role of village officials has a positive effect on the accountability of village fund management.